2011
DOI: 10.1038/pcan.2011.48
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the localization of fibroblast growth factor 9 in prostate cancer cells and postoperative recurrence

Abstract: BACKGROUND: Fibroblast growth factor 9 (FGF9) enhances cell proliferation and invasiveness in several malignant diseases. The aim of the present study is to investigate the role of FGF9 in postoperative recurrence after radical prostatectomy. METHODS:Cell viability and invasion of LNCaP cells were assessed using MTT assay and Matrigel invasion assay, respectively, in the presence or absence of treatment with recombinant FGF9. Tissues obtained during a radical prostatectomy in 133 male patients were immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…However, it has also been discovered to facilitate gastric cancer invasion and growth . Besides, FGF9 was believed to indicate a poor prognosis of non‐small‐cell lung cancer, colon cancer, and prostate cancer . However, we found that FGF9 was underexpressed in LSCC tissues, which suggested its tumor suppressor role rather than a tumor facilitator role.…”
Section: Discussionmentioning
confidence: 65%
“…However, it has also been discovered to facilitate gastric cancer invasion and growth . Besides, FGF9 was believed to indicate a poor prognosis of non‐small‐cell lung cancer, colon cancer, and prostate cancer . However, we found that FGF9 was underexpressed in LSCC tissues, which suggested its tumor suppressor role rather than a tumor facilitator role.…”
Section: Discussionmentioning
confidence: 65%
“…Despite previous studies by us and others showing rigid regulations at pre- (22,23) and post-transcriptional levels (24,25), overexpressed FGF9 protein is frequently observed in various cancer cells (17–20). Although aberrant expression of FGF9 is known to promote cancer progression in many cancers including colon cancer (36–38), the mechanism of how FGF9 protein is elevated in cancer cells remains largely unknown. As translational control provides cells with the plasticity and flexibility to respond to rapid changes in the environment, we hypothesized the increase of FGF9 protein resulted from the response to the microenvironmental change (i.e.hypoxia) in the cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of cells stained and the staining intensity score were assessed by the pathologist as follows: 0, absence of staining; 1, weakly stained; 2, moderately stained; and 3, strongly stained. The total score was calculated by multiplying the proportion score with the intensity score [2, 36, 37]. High expression of FGF9 means that the expression of FGF9 is higher than that of normal tissue adjacent to cancer.…”
Section: Methodsmentioning
confidence: 99%